Developing a Modified Volleyball-Based Learning Model to Improve Students’ Engagement in Physical Education - Sahabuddin, Sahabuddin; Sofyan, Davi; Lengkana, Anggi Setia (JOURNAL RESPECS (Research Physical Education and Sports), 2025)
Learning modelThis study aimed to develop and evaluate a modified volleyball-based learning model (V-ENGAGE) to enhance student engagement in physical education (PE) at SMK Negeri 7 Makassar. Using a research and development (R&D) design with a quantitative pretest-posttest approach, data were collected from 60 students through engagement questionnaires and performance-based volleyball skill tests. The V-ENGAGE model integrates modified games, collaborative tasks, reflective discussions, and contextual relevance tailored to vocational high school settings. Results showed a significant increase in student engagement across behavioral, emotional, and cognitive domains. The average engagement score improved from 64.2 (pretest) to 83.7 (posttest), indicating a 30.3% enhancement. Volleyball skills also improved, with mean scores rising from 68.5 to 86.1 in the final assessment (p < 0.01). These findings suggest that the V-ENGAGE model effectively boosts both engagement and learning outcomes in PE. The study concludes that a modified volleyball learning model, when pedagogically aligned to students’ needs and school context, can promote meaningful and active participation in physical education. The model can serve as a strategic tool for PE teachers to improve student motivation and performance.